Risk and Resilience in Tourism: How Political Instability and Social Conditions Influence Destination Choices - Panagiotis Grigoriadis; Asimenia Salepaki; Ioannis Angelou; Dimitris Kourkouridis (Tourism and Hospitality, 2025)
In an era of increasing global uncertainty, tourism destinations face significant challenges due to political instability and social unrest, which shape travelers’ perceptions and decision making. This study examines the relationship between perceived risk, resilience, and destination choice, focusing on the extent to which political and social conditions influence travel intentions. Using the social amplification of risk framework (SARF) and a quantitative survey, this research identifies key determinants of tourism resilience and risk perception management. Our findings indicate that political instability, safety concerns, and negative media coverage deter travelers, while effective crisis communication, strong governance, and high-quality public services can enhance a destination’s appeal. Based on these findings, the study recommends that destination marketers and tourism policymakers invest in targeted safety communication, service quality improvements, and strategies that address the specific concerns of more risk-sensitive demographics, such as women. The study offers strategic insights for destination marketers, tourism policymakers, and hospitality stakeholders on how to mitigate perceived risks and foster resilience in tourism-dependent economies. Future research could explore cross-cultural traveler behavior and incorporate perspectives from tourism professionals to further inform resilience strategies. By addressing these challenges, destinations can develop sustainable strategies to navigate crises and maintain competitiveness in an unpredictable global landscape.